Persea psammophila (Lauraceae), a New Species from Bahia, Brazil - Rodrigues De Moraes, Pedro Luís [UNESP]; Trinca, Mayra Deltreggia [UNESP] (American Society of Plant Taxonomists, 2021)
Persea psammophila , a new species of Lauraceae collected near the border between the states of Bahia, municipality of Maiquinique, and Minas Gerais, municipality of Jordânia, Brazil, is described and illustrated. The new species belongs to Persea subg. Eriodaphne. It is distinguished from other Neotropical Persea species by the treelet habit in combination with sparsely pubescent twigs, elliptic to mainly obovate leaves, adaxially glabrous, abaxially sparsely pubescent and papillose, sparsely pubescent inflorescences, pubescent, relatively small flowers, and floral parts smaller than congeneric species in the Atlantic rainforest. Its putative relationships within the genus are discussed. Illustrations and comments on micromorphological and anatomical features of leaves of this new species are provided, comparing them to those of congeners.
Keywords: Atlantic rainforest; leaf cuticles; leaf vasculature; leaf venation; Persea subg. Eriodaphne; taxonomy